2018
DOI: 10.1007/s12094-018-1925-1
|View full text |Cite
|
Sign up to set email alerts
|

Active study: undetected prevalence and clinical inertia in the treatment of breakthrough cancer pain (BTcP)

Abstract: Clinical inertia is a serious problem in the handling of BTcP in medical oncology services, where it is the subject of a significantly low level of detection and treatment, despite the contrasting perception of specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Clinical presentation is heterogeneous, and therefore, breakthrough pain cannot be considered as a single entity. However, uniform breakthrough pain has an important impact on a patient’s functionality, which supports the need for early detection and treatment, especially considering that some surveys indicate that breakthrough pain is frequently undetected 17 and undertreated 24,28 , and our results indicate that over 40% of patients are able to foretell the occurrence of BTP episodes.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Clinical presentation is heterogeneous, and therefore, breakthrough pain cannot be considered as a single entity. However, uniform breakthrough pain has an important impact on a patient’s functionality, which supports the need for early detection and treatment, especially considering that some surveys indicate that breakthrough pain is frequently undetected 17 and undertreated 24,28 , and our results indicate that over 40% of patients are able to foretell the occurrence of BTP episodes.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, in a recent study conducted by 108 medical oncologists, Camps et al . reported a prevalence of 91% of BTP using the Davies algorithm 17 . We think that the selection of patients in that study could explain, at least in part, this high prevalence of BTP; these authors selected patients who, before the start of the study, had been treated by the participant oncologists as patients suffering some kind of cancer-related pain 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a study by the American Pain Foundation showed that living with pain negatively infl uences emotional health and causes suffering in 82% of patients [25]. However, despite its prevalence and impact on patients, BTcP is sometimes unrecognized and often undertreated [26][27][28]. Prompt and effi cient diagnosis is therefore essential.…”
Section: Diagnostic Criteriamentioning
confidence: 99%